Body size from birth to adulthood as a predictor of self-reported polycystic ovary syndrome symptoms. - Laitinen, J; Taponen, S; Martikainen, H; Pouta, A; Millwood, I; Hartikainen, A; Ruokonen, A; Sovio, U; McCarthy, M; Franks, S; Järvelin, MR (2003)
OBJECTIVE: To study the association between body size from birth to adulthood and self-reported symptoms of polycystic ovary syndrome (PCOS), particularly hirsutism and menstrual disturbances. DESIGN: Longitudinal, population-based study of a cohort of women born in 1966 in northern Finland. The study population included 2007 women who were not pregnant and did not use hormonal contraception. Of these 528 (26%) had self-reported symptoms of PCOS. RESULTS: Weight at birth, gestational age, being small for gestational age or growth retardation at birth were not associated with PCOS symptoms at 31 y. An increased risk of PCOS symptoms was observed among women with abdominal obesity (waist/hip ratio >85th percentile) at 31 y who had normal weight in adolescence and were overweight (body mass index (BMI) 25.0-29.9 kg/m(2)) or obese (BMI>30.0 kg/m(2)) at 31 y (relative risk (RR) (95% CI) 1.44(1.10-1.89)), and among women with abdominal obesity who were overweight or obese at both 14 and 31 y (1.71 (1.30-2.24)). A total of 30% and 41% of the women with PCOS symptoms in these groups could be attributed, respectively, to overweight, obesity and abdominal obesity at 31 y. CONCLUSIONS: These results suggest that obesity in adolescence and in adulthood, and also weight gain after adolescence, particularly in the presence of abdominal obesity, are associated with self-reported PCOS symptoms in adulthood. Thus, based on the results from intervention studies treating PCOS and the results of this study, the prevention of obesity and abdominal obesity is important among young women.